Reduced Tax Progressivity in Norway in the Nineties The Effect from Tax Changes - Thor O. Thoresen (Statistics Norway, Research Department, 2002)
The inequality in pre-tax income increases in Norway in the 1990s, while the distribution of taxes is about unaltered. This means that tax progressivity has decreased in the period, as measured by summary indices of tax progressivity. This paper discusses to what extent this observed decrease in tax progressivity can be explained by tax changes in the period, by analysing individual income data. As marginal tax rates at high income levels have been substantially reduced in the period, for instance through the tax reform of 1992, it is expected that tax changes may have influenced the degree of inequality in pre-tax incomes. This behavioral effect is examined by deriving tax elasticity estimates, obtained from various panel data set regressions. Moreover, the tax changes may also have shifted the distributional burden of taxes for unaltered level of pre-tax income inequality. In order to identify this (direct) effect of tax-law alterations, the same fixed distribution of pre-tax income is exposed to various tax-laws in the period.
Keywords: H24; H31; J22; 330; tax progressivity; progressivity measures; tax elasticity estimates; panel data; random effects model; fixed effects model